The Development of Social Security Law for Foreign Workers Legally Working in Thailand - Navasanti, Ruengdaj; Santaswang, Nut; Chokmoh, Poom; Phipatanatkul, Phaisith (Ph.D. in Social Sciences Journal, 2023)
This research article aims to study (1) the concepts and theories related to social security law; (2) problem regarding the rights under the social security law of foreign workers who are legally allowed to work in Thailand; (3) analyze and compare the laws and rights in the social security system of migrant workers who come to work legally in Thailand and abroad; and (4) find appropriate ways to develop social security laws to provide social security protection for foreign workers who are legally permitted to work in Thailand by using a qualitative research method and collecting data through documentary research, in-depth interviews and focus group discussion and analyzed the data by using content analysis techniques and comparison interpretation. Findings are as follows: The development of social security law for foreign workers legally working in Thailand. The Social Security Act, B.E. 2533 must be amended to have a definition that “foreign employee” and “registered foreign worker” for clarity in interpretation and legal measures in exercising the social security rights of foreign workers who come to work legally in Thailand. (in case of encountering danger or sickness not due to work, childbirth, child support, unemployment and old age) Including foreign workers who are legally allowed to work in Thailand who travel out of the Kingdom have the right to social security protection continuously, but must not exceed one year from the last payment of contributions by the workers. And the penalty for employers avoiding registration of employees or not sending social security contributions is to have imprisonment and a more severe fine.